Financial education programs as a mechanism to achieve financial Inclusion. The experience of the National Center for Financial Education NCFE (India) - Naamane BAHLOUL; Imad SIHAMDI (المجلة الدولية للأداء الاقتصادي, 2023)
This paper examines the role of the National Centre for Financial Education in promoting financial literacy and inclusion among low-income families in India. The study is based on a comprehensive review of existing literature and available statistics on Indian NCFE coders. The analysis reveals that these programmes have the potential to significantly improve financial culture and inclusion and that financial technology platforms have a role in promoting responsible financial behaviour.